Parties and party systems in Latin America: perspectives from an Expert Survey 2009 - Altman, David; Luna, Juan Pablo; Piñeiro, Rafael; Toro, Sergio (Revista de Ciencia Política, 2020)
This research note presents a classification of Latin American parties and party systems, according to mainstream ideological currents and country-specific competitive patterns. This classification is based on a preliminary analysis of the results of an expert survey on Latin American party systems that was carried out from 2007 to 2009. We factor-analyze parties’ positions on a wide set of issues and estimate three (latent) ideological dimensions: statism, conservatism (moral, religious, nationalist), and attitudes towards democracy. On the basis of these three ideological dimensions we perform a cluster analysis and classify the political parties of the region in ten “ideological families”.